Ultrasmall microdisk and microring lasers based on InAs/InGaAs/GaAs quantum dots - Maximov, Mikhail V (Nanoscale Res Lett, 2014)
ABSTRACT: Ultrasmall microring and microdisk lasers with an asymmetric air/GaAs/Al(0.98)Ga(0.02)As waveguide and an active region based on InAs/InGaAs/GaAs quantum dots emitting around 1.3 μm were fabricated and studied. The diameter D of the microrings and microdisks was either 2 or 1.5 μm, and the inner diameter d of the microrings varied from 20% to 70% of the outer diameter D. The microring with D = 2 μm and d = 0.8 μm demonstrated a threshold pump power as low as 1.8 μW at room temperature. Lasing was observed up to 100°C owing to the use of quantum dots providing high confinement energy both for electrons and holes. Tuning spectral positions of the whispering gallery modes via changing the inner diameters of the microrings was demonstrated. PACS: 78.67.Hc; 42.55.Sa; 42.50.Pq; 78.55.Cr ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1556-276X-9-657) contains supplementary material, which is available to authorized users.